2017
DOI: 10.1007/s11547-017-0819-6
|View full text |Cite
|
Sign up to set email alerts
|

Unindicated multiphase CT scans in non-traumatic abdominal emergencies for women of reproductive age: a significant source of unnecessary exposure

Abstract: In our experience, unindicated additional CT phases were numerous with a significant excess radiation dose without an associated clinical benefit. This excess of radiation could have been avoided by widespread adoption of the ACR appropriateness criteria and evidence-based data from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Although prior studies have reported on the frequency of multiphase CT protocols and the associated radiation dose, these studies focused on single-institutional data from most developed countries. 2,10 -14 In contrast, our study reports the frequency and radiation dose burden associated with the multiphase scanning in multiple institutions from the developing countries in 4 continents. The lack of justification for multiphase CT reported in our study is similar to those in prior studies.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Although prior studies have reported on the frequency of multiphase CT protocols and the associated radiation dose, these studies focused on single-institutional data from most developed countries. 2,10 -14 In contrast, our study reports the frequency and radiation dose burden associated with the multiphase scanning in multiple institutions from the developing countries in 4 continents. The lack of justification for multiphase CT reported in our study is similar to those in prior studies.…”
Section: Discussionmentioning
confidence: 96%
“…The lack of justification for multiphase CT reported in our study is similar to those in prior studies. 2,10 -14 For example, Guite et al reported that 61% patients (307/500) had multiphase abdomen–pelvis CT, and 86% (264/307) of these patients had at least one unjustified phase per ACR Appropriateness criteria. 2 We also observed that 2 of 3 of the multiphase abdomen–pelvis CT had one or more unjustified phases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This parameter can be quantitatively defined and derived by DWI images expressing the entity of tissues restriction of diffusion (35). The strong point of DWI compared to dynamic contrast enhanced (DCE)-MRI is its high sensitivity to identify histological changes in the microscopic environment without need for contrast medium administration, which should be avoided in cases of pregnancy and impaired renal function (36)(37)(38)(39)(40).…”
Section: Basic Physics Of Diffusion-weighted Imaging (Dwi)mentioning
confidence: 99%